Pengaruh Return on Equity, Debt to Equity Ratio, dan Corporate Social Responsibility terhadap Nilai Perusahaan - Inas, Dhiya Hanun Azhar; Atmojo, Purwo; Sutadji, Ika Makherta; Saraswati, Wiwik (Universitas Gorontalo, 2025)
This study aims to determine the effect of Return On Equity, Debt to Equity Ratio, and Corporate Social Responsibility on firm value. The population in this study are food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2021-2023. Data collection using documentation techniques. Sample selection using purposive sampling method. The sample of this study consisted of 32 companies during the 2021-2023 period. Data collection is based on the company's annual report and sustainability report and after data outliers, the total sample in this study amounted to 66 samples. The analysis method used in this study is multiple linear regression analysis, classical assumption test, and hypothesis testing using SPSS 26. The results of this study indicate that return on equity affects firm value, corporate social responsibility affects firm value, while debt to equity ratio has no effect on firm value. Simultaneously, return on equity, debt to equity ratio, and corporate social responsibility affect firm value.